HOMO SACER AS ILLUSTRATED ON KYA ON THE FILM WHERE THE CRAWDADS SING - Vivi Nur Aini Susanto; Axlinabila Annisa Anasai; Hariyono; Rommel Utungga Pasopati (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Film relates to the identity of each person's character. Kya is the leading character in the film Where the Crawdads Sing. Homo Sacer describes the pejorative previous identity of a person who can be very influential in society. Where the Crawdads Sing was adapted from a novel by Delia Owens that raised a person's life who must be sacrificed as a suspect in a murder case. This film focuses on Kya who earned the nickname 'Marsh Girl' since she lived in a marsh that was so far from settlements. Kya almost never interacts with other people. She has been isolated since childhood, lives without a family, and supports herself alone. Thus, how is Homo Sacer illustrated in Kya on the film Where the Crawdads Sing? By using qualitative method, this article focuses on the character of Kya as a 'Marsh Girl' that is illustrated by the concept of Homo Sacer by Giorgio Agamben. Agamben describes how his ideas on sovereign power and bare life could help in understanding contemporary issues. In conclusion, this film depicts a person's character related to the concept of Homo Sacer viewed through Kya as the labelled character.